Fertility impairment associated with uterine fibroids – a review of literature - Lisiecki, Marek; Paszkowski, Maciej; Woźniak, Sławomir (Menopause Review/Przegląd Menopauzalny, 2017)
Uterine fibroids (also known as leiomyomas or myomas) are the most common benign tumors affecting reproductive organs in women. They are monoclonal tumors of the uterine smooth muscle, which spring from myometrium. It is estimated that they occur in 50-60% of the female population and rise to 70% by the age of 50. While mostly asymptomatic, myomas can be connected with several conditions, including abnormal bleeding with subsequent anemia, pelvic masses, pelvic pain, bulk symptoms, unfavorable impact on fertility and obstetric complications. Factors, which predispose the emergence of fibroids are: hormones, Afro-American ethnicity, age, obesity, adverse pregnancy outcome history, early menarche, genetic factors, alcohol, caffeine or eating too much red meat. On the other hand, there are factors, which can decrease this risk: pregnancy, early menopause and tobacco smoking. There are several mechanisms of fertility impairment in females with fibroids: alternations in uterus function (flawed blood supply, increased contractility), changes in the normal uterus anatomy, local hormonal changes induced by fibroids. In this review the connection between fibroids and infertility is analyzed.